2015
DOI: 10.1080/01932691.2015.1004185
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Viewpoint of Imidazolium Salts for Selective Extraction of Cobalt in the Presence of Nickel from Acidic Thiocyanate Solutions by Ionic-Liquid-Based Solvent-Extraction Technique

Abstract: In this study, the selective extraction and stripping conditions of Co(II) from acidic thiocyanate solution containing Co(II) and Ni(II) by ionic liquid based solvent extraction technique (ILBSX) using symetric and asymetric imidazolium bromide salts substituting butyl and isobutyl groups were experimentally optimized. The molecular structure effect of IMs have been determined as main factor to extract Co(II). The executive parameters on stripping and extraction processes such as IMs concentration, pH, thiocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 87 publications
0
5
0
1
Order By: Relevance
“…Solangi et al [38] have reported the transportation of Cr(VI) across SLMs containing p-tert-butylcalix [4]arene diamide. Some investigators have studied the effect of ionic liquids as alternative for conventional volatile organic solvents in order to separation of different metals in different processes [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Solangi et al [38] have reported the transportation of Cr(VI) across SLMs containing p-tert-butylcalix [4]arene diamide. Some investigators have studied the effect of ionic liquids as alternative for conventional volatile organic solvents in order to separation of different metals in different processes [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Using them as catalyzer, extractant, solvent, electrolyte, surfactant, plasticizer, inhibitor, etc. is the only limited usage of ILs as we know, and many different usage fields about ILs has been already discovered in every day . The percent rate of RTILs among the IPM composition was investigated in the range of 0–35.7% (w/w), and P values of a kinetic parameter were given in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eyupoglu et al. used four imidazolium‐based ionic liquids with different alkyl groups in mildly acidic aqueous solutions containing thiocyanate as the complexing agent [103] . They reported 1,3‐dibutylimidazolium bromide can extract Co with a very high selectivity of 2000 000 even in mild acidic media.…”
Section: Disruptive Potential Of Ionic Liquids For Space Resourcesmentioning
confidence: 99%